Pembangunan Aplikasi E-Commerce Pemasaran Batik pada Toko Batik Rifqi - Angger Wibowo; Aziz Setyawan Hidayat; Eva Rahmawati (Journal of Computer System and Informatics (JoSYC), 2020)
The use of the internet in the business world serves as a business strategy application, such as: marketing, sales, and customer service. This is evidenced by the many large companies that have used or used the internet for business development, for example, online stores. In doing business, entrepreneurs are faced with challenges as to how they can serve and provide the required information to customers quickly, without being limited by place, distance and time. it happens because of influential factors such as company location, limited operating hours, lack of product information can reduce the number of transactions and can even cause customers to switch to other companies better. The system development method used is SDLC (System Development Life Cycle), namely software requirements analysis, design, code generation, testing, support, or maintenance. MySQL as a database for PHP applications. With this e-commerce website, it is expected to make it easier for buyers to be able to buy batik that is sold in stores easily via the internet. With this website the seller can easily promote a wider range of people